2015
DOI: 10.1159/000441427
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Clinical Features and Factors Associated with Pouchitis after Proctocolectomy with Ileo-Pouch-Anal Anastomosis in Patients with Ulcerative Colitis: A Latin-American Country Retrospective-Cohort Study

Abstract: Background: Pouchitis is the most common complication of proctocolectomy with ileo-pouch-anal anastomosis (IPAA) for ulcerative colitis (UC). No previous study in Mexico has evaluated this issue; our aim was to evaluate its frequency, clinical characteristics and factors associated with its presence in Mexican patients with UC and IPAA. Methods: Retrospective-cohort study including 70 patients with histopathological diagnosis of UC and IPAA between 1983 and 2014 from inflammatory bowel disease clinic of a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…No relevant RCTs were retrieved. Nine and 11 observational studies were selected for the analysis of chronic pouchitis and overall pouchitis respectively in relation to EIMs ( Table S1 , supporting information), and six and ten studies respectively in relation to PSC ( Table S2 , supporting information). One study included both ulcerative colitis and familial polyposis.…”
Section: Resultsmentioning
confidence: 99%
“…No relevant RCTs were retrieved. Nine and 11 observational studies were selected for the analysis of chronic pouchitis and overall pouchitis respectively in relation to EIMs ( Table S1 , supporting information), and six and ten studies respectively in relation to PSC ( Table S2 , supporting information). One study included both ulcerative colitis and familial polyposis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 15 manuscripts, 12 were retrospective studies, 4,[12][13][14][15][20][21][22][23][24][25][26] 2 were prospective 27,28 and 1 was case-control. 29 Twelve studies included ulcerative colitis patients only [12][13][14][15][20][21][22][23][24][25][26][27] ; three studies included both ulcerative colitis and indeterminate colitis patients. 4,28,29 A total of 2,276 IPAA patients were included in the systematic review and meta-analysis.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…Three studies have shown that smoking may have a protective benefit, 13,[26][27][28] one study has shown a harmful effect 15 and eleven studies have failed to show statistically significant differences in pouchitis rates between smokers and nonsmokers. 4,12,14,16,[20][21][22][23][24][25]29 Notably, all except two of these studies were retrospective and sample sizes varied widely, from 10 to 353 subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of pouchitis after IPAA ranges from 30% to 50% . Patients with pouchitis often present with many nonspecific symptoms, such as increased stool frequency, urgency, incontinence, nocturnal seepage, abdominal cramping, pelvic discomfort, and arthralgia . In some cases, the diagnosis of pouchitis is somewhat intricate because relatively mild symptoms are not necessarily associated with severe endoscopic or histological pouch inflammation.…”
Section: Introductionmentioning
confidence: 99%